ANILLOS DE BOOLE - Ruiz Salguero, Carlos; Departamento de Matemáticas Facultad de Ciencias Pontificia Universidad Javeriana (2013)
Applaying thl theory of adjoint functions and adjoint functors ! / en basic concepts of Boolean Algebra are revised.